Recent advancements in nano sensors for air and water pollution control - Anita Grozdanov,1 Perica Paunović,1 Iva Dimitrievska,1 (MedCrave, 2023)
Increased environmental pollution is becoming one of the greatest problem the world is facing nowadays causing irreparable damage to the earth. Because of their novel and tunable physicochemical properties, nano materials have attracted great attention among researchers as promising materials to combat environmental challenges. Developing nanotechnology have triggered a great deal of interest in these structures for pollution monitoring and treatment, enabling new technologies for identifying and addressing environmental problems. Even though achieving environmental pollution control is a challenging task using conventional materials, revolutionary progress has been observed with the advancements in nanotechnology, showing that precisely modified nano materials can be used for purposes such as treatment of polluted atmosphere, industrial and domestic wastewater, natural water, and soil. In this paper we review and discuss the environmental applications of nano materials as nano sensors employed for combating atmospheric and aquatic pollution.
Keywords: environmental pollution, sensors, nano materials, water contamination, air pollution